A Rare Malignancy of Para nasal Region; Osteosarcoma - M.D., Selçuk Kuzu (International Journal of Innovative Research in Medical Science, 2017)
In the practice of otorhinolaryngology mass in nasal cavity is often seen. According to other regions, malign tumors of the paranasal region and nasal cavity are very rare. Osteosarcomas constitute 0.5-1% of all tumors in the nasal cavity and paranasal sinuses. In this study, we report a case of maxillary osteosarcoma causing recurrent epistaxis.